The PAZOREAL noninterventional study to assess effectiveness and safety of pazopanib and everolimus in the changing metastatic renal cell carcinoma treatment landscape - Goebell, Peter Jürgen; Grüllich, Carsten (Future oncology, 2017)
VEGFR and mTOR inhibitors are broadly used in metastatic renal cell carcinoma (mRCC) therapy, and sequential first-line pazopanib (VEGFR inhibitor) and second-line everolimus (mTOR inhibitor) is a standard treatment option. Nivolumab and lenvatinib/everolimus combination was recently approved in Europe for use in mRCC after previous therapy. Prospective routine data on sequential therapy including nivolumab and/or lenvatinib are missing. This is a prospective, noninterventional study, which evaluates the effectiveness, tolerability, safety and quality of life following 450 patients with mRCC starting either on pazopanib as first-line therapy or third-line everolimus plus/minus lenvatinib following nivolumab. Adults with histologically confirmed mRCC of any subtype, who have a life expectancy of at least 6 months, are eligible.